(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article explores the effectiveness of innovative teaching methods in fostering independent thinking skills among primary school students. In the context of rapid educational modernization and increasing emphasis on learner-centered pedagogy, the development of independent thinking has become a crucial component of early education. The study examines how modern instructional approaches—such as problem-based learning, project-based tasks, interactive technologies, creative learning activities, and differentiated instruction-enhance students’ ability to analyze information, generate personal viewpoints, make autonomous decisions, and solve problems creatively. Through a combination of theoretical investigation and practical experimentation, the research identifies the pedagogical conditions necessary for cultivating independence in young learners. An innovative teaching model designed for primary education was developed and tested, integrating cognitive activation strategies, inquiry-based learning, and reflective practices. Experimental results demonstrate that students exposed to innovative methods exhibit higher levels of motivation, creativity, responsibility, and decision-making abilities. The findings also show that the introduction of digital tools and interactive techniques significantly contributes to the formation of critical and independent thinking at an early age.